Engineering and characterisation of BCG-loaded polymeric microneedles. (27th May 2020) - Arshad, Muhammad Sohail; Fatima, Sameen; Nazari, Kazem; Ali, Radeyah; Farhan, Muhammad; Muhammad, Syed Aun; Abbas, Nasir; Hussain, Amjad; Kucuk, Israfil; Chang, Ming-Wei; Mehta, Prina; Ahmad, Zeeshan
Abstract: The aim of this study was to fabricate Bacillus Calmette–Guérin (BCG)-loaded microneedle patches using micromould casting technique and compare their efficacy with the injectable counterparts. The microneedle patches were formulated using sodium alginate (10% w/v) and trehalose (20% of polymer). The patches were characterised using optical microscopy, scanning electron microscopy and folding endurance. Serum IgG, TLC, granulocyte count, lymphocyte count and CRP were assessed and results were compared to that of intradermal injections alongside controls. The results showed that polymeric patches had a thickness of 0.8 mm, microneedle projections of 272 ± 12 µm and folding endurance of more than 300. Based on haematological and IgG ELISA assays, microneedle-based BCG administration significantly activated the immune cells and induced production of lymphocytes, granulocytes and peptide-specific IgG in immunised rats that were comparable to injectable counterparts. There was an increase in IgG antibodies from 3 g/L to 5.98 g/L and an increase in leucocytes from 2.6 × 10 9 /L to 18.45 × 10 9 /L. There was also an increase in granulocytes from 14.4% to 29.15% and lymphocyte count from 58.75% to 85.3%. It was concluded that BCG-coated polymeric microneedle patches are suitable for the transdermal delivery of vaccine without inducing discomfort usually observed with injections.